Adaptation to Loudness and Environmental Stimuli in Three Newly Fitted Hearing Aid Users - Lindley, George A., IV; Palmer, Catherine V.; Durrant, John; Pratt, Sheila (Journal of the American Academy of Audiology, 2000)
Hearing aid fitting strategies can be categorized according to whether a loudness normalization or a loudness equalization rationale is employed. Regardless of the underlying rationale, the amount of patient participation in determining the initial hearing aid settings will vary when an audiologist-driven (AD) versus a patient-driven protocol is employed. When an AD protocol is used, few changes are made during the initial fitting session based on user feedback. It is assumed that the patient will adapt to the loudness and/or sound quality provided by the hearing aids if not immediately acceptable. The following three case reports document varying degrees of adaptation to hearing aid settings derived using an AD approach. Clinical implications will be discussed.Abbreviations: AD = audiologist driven, DSL [i/o] = Desired Sensation Level input/output, EN = environmental noise subscale, HINT = Hearing in Noise Test, IHAFF = Independent Hearing Aid Fitting Forum, LE = loudness equalization, LN = loudness normalization, PD = patient driven, PHAP = Profile of Hearing Aid Performance, RAB = Ricketts and Bentier, SII = Speech Intelligibility Index, WDRC = wide dynamic range compression
Keywords: Adaptation; fitting protocols; hearing aids; sensorineural hearing loss